Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1590/fst.10420
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring environmental microbiological safety in a frozen fruit and vegetable plant

Abstract: Ensuring food safety is becoming progressively important in frozen foods due to increased demand and consumption worldwide. The Environmental Monitoring Program (EMP) shall support daily operational activities and monitor the lack of process hygiene & sanitation actions to achieve food safety. The aim of this study was implementation of EMP in the frozen fruit and vegetable factory to identify the place that allows for pathogen/indicator microorganism growth and create preventive actions to reduce or eliminate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
3
0
1
Order By: Relevance
“…Data collected at different surfaces indicated that the concentration of SARS‐CoV‐2 varied from 0.1 to 102.4 gc/cm 2 (Abrahão et al., 2021; Harvey et al., 2020). For E. coli , the concentration varied from 0.1 to 15.8 CFU/cm 2 (Cinar & OnbaŞI, 2021; Trindade et al., 2014) on contaminated surfaces at healthcare facilities. In this study, the initial concentration of SARS‐CoV‐2 and E. coli are assumed to be 100 gc/cm 2 and 10 CFU/cm 2 , respectively.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…Data collected at different surfaces indicated that the concentration of SARS‐CoV‐2 varied from 0.1 to 102.4 gc/cm 2 (Abrahão et al., 2021; Harvey et al., 2020). For E. coli , the concentration varied from 0.1 to 15.8 CFU/cm 2 (Cinar & OnbaŞI, 2021; Trindade et al., 2014) on contaminated surfaces at healthcare facilities. In this study, the initial concentration of SARS‐CoV‐2 and E. coli are assumed to be 100 gc/cm 2 and 10 CFU/cm 2 , respectively.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…Hal ini dapat mengakibatkan penurunan kualitas maupun risiko tercemar mikroba (Cai et al, 2019). Meskipun pada akhirnya kembali disimpan dalam kondisi beku, namun sifat fisik produk tetap tidak dapat kembali seperti semula, sedangkan apabila sampai ditumbuhi mikroba, maka mikroba akan tetap berada pada produk pangan dan membahayakan konsumen (Cinar & Onbaşi, 2021). Hasil pengukuran perbedaan pengetahuan mitra sebelum dan sesudah penyuluhan dapat dilihat pada Tabel 1.…”
Section: Hasil Dan Pembahasanunclassified
“…Given this issue and the growing importance of food security in recent years, the attention of the general public and regulatory bodies in the food sector, especially the World Trade Organization, has seriously focused on food safety and quality assessment (Cinar & Onbaşi, 2020). Obviously, the food safety chain in any country must be maintained from the farm to the family table, and in the meantime, the livestock sector plays an important role in food security as well as the agricultural and economic development of countries.…”
Section: Investigation Of Possible Hazards Associated With Animal Pro...mentioning
confidence: 99%